The bridge of the gut–joint axis: Gut microbial metabolites in rheumatoid arthritis - Xu, Xiaoyu; Wang, Miao; Wang, Zikang; Chen, Qian; Chen, Xixuan; Xu, Yingyue; Dai, Min; Wu, Bin; Li, Yanping (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by joint destruction, synovitis, and pannus formation. Gut microbiota dysbiosis may exert direct pathogenic effects on gut homeostasis. It may trigger the host's innate immune system and activate the "gut–joint axis", which exacerbates the RA. However, although the importance of the gut microbiota in the development and progression of RA is widely recognized, the mechanisms regulating the interactions between the gut microbiota and the host immune system remain incompletely defined. In this review, we discuss the role of gut microbiota-derived biological mediators, such as short-chain fatty acids, bile acids, and tryptophan metabolites, in maintaining intestinal barrier integrity, immune balance and bone destruction in RA patients as the bridge of the gut–joint axis.